2010
DOI: 10.1111/j.1553-2712.2010.00755.x
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Ultrasound by Paramedics: Results of Field Trial

Abstract: Objectives: The objective was to determine if 9-1-1 paramedics trained in ultrasound (US) could adequately perform and interpret the Focused Assessment Sonography in Trauma (FAST) and the abdominal aortic (AA) exams in the prehospital care environment.Methods: Paramedics at two emergency medical services (EMS) agencies received a 6-hour training program in US with ongoing refresher education. Paramedics collected US in the field using a prospective convenience methodology. All US were performed in the ambulanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
71
2
5

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(83 citation statements)
references
References 20 publications
5
71
2
5
Order By: Relevance
“…There was one study in the English literature about paramedicperformed FAST, but it was designed in the prehospital area and for prehospital triage. [26] We found that our results were well correlated with this study as well. A literature search showed that USG performed by healthcare personnel other than doctors, such as nurses and paramedics, was accurate in other areas such as intravenous cannula insertion, echocardiography, abdominal aortic aneurysm detection, and obstetric USG.…”
Section: Discussionsupporting
confidence: 90%
“…There was one study in the English literature about paramedicperformed FAST, but it was designed in the prehospital area and for prehospital triage. [26] We found that our results were well correlated with this study as well. A literature search showed that USG performed by healthcare personnel other than doctors, such as nurses and paramedics, was accurate in other areas such as intravenous cannula insertion, echocardiography, abdominal aortic aneurysm detection, and obstetric USG.…”
Section: Discussionsupporting
confidence: 90%
“…During this period, focus has swerved toward using ultrasound in the ED and in the pre-hospital setting [16,17]. The E-FAST (Extended Focused Assessment Sonography in Trauma) is affirmed as well as using in patients with major trauma [18].…”
Section: Discussionmentioning
confidence: 99%
“…With thorough training and close supervision, medics can adequately obtain and interpret prehospital ultrasound images [23]. A simulation trial demonstrated that ultrasound-naive practitioners were able to achieve an acceptable standard of competency in a relatively short period of time for both acquisition and interpretation of images [24].…”
Section: Prehospital Emergency Medical Servicesmentioning
confidence: 99%